2017
DOI: 10.7150/ijms.19033
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antitumor Effect of Sorafenib in Combination with ATM Inhibitor in Hepatocellular Carcinoma Cells

Abstract: Background: Currently, sorafenib is the only systemic chemotherapy drug for advanced stage Hepatocellular carcinoma (HCC). However, emerging data from some clinical HCC patients indicate that sorafenib alone has only moderate antitumor efficacy, and could not inhibit disease metastasis and progression. KU-55933 is a specific ATM inhibitor, which has pro-apoptotic effect on tumor cells. In this study, we analyzed the synergistic effect of sorafenib and KU-55933 on the proliferation of HCC cell lines.Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The dose response curves of Sora in HepG2 and Huh7 cells were similar to those reported previously, with IC 50 values of 5.93–8.51 (mean 7.10) µM in HepG2 and 7.11–17.11 (mean 11.03) µM in Huh7 cells (Fig. 1; Table I) (20,21). It has been reported that the maximum drug concentration of Art in human plasma is 3,260 (1,020–164,000) ng/ml [8.48 (2.65–427.08) µM] and the terminal elimination half-life is 0.25 (0.1–1.8) h (22).…”
Section: Resultssupporting
confidence: 87%
“…The dose response curves of Sora in HepG2 and Huh7 cells were similar to those reported previously, with IC 50 values of 5.93–8.51 (mean 7.10) µM in HepG2 and 7.11–17.11 (mean 11.03) µM in Huh7 cells (Fig. 1; Table I) (20,21). It has been reported that the maximum drug concentration of Art in human plasma is 3,260 (1,020–164,000) ng/ml [8.48 (2.65–427.08) µM] and the terminal elimination half-life is 0.25 (0.1–1.8) h (22).…”
Section: Resultssupporting
confidence: 87%
“…CADMN after 72 h of treatment exhibits a significant cytotoxic effect against HepG2 hepatocellular carcinoma cells with IC 50 17.1 ± 0.592 μM, which is comparable to the positive control 5-FU (IC 50 14.6 ± μM). Previous studies have reported the antiproliferative effects of other chemotherapeutic agents such as sorafenib, a targeted therapy for HCC, and revealed that sorafenib inhibits HepG2 cells with an IC 50 between 7.4 and 2 μM [ 28 , 29 ], which is much lower than that of CADMN and 5-FU.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib is the only anticancer drug approved by the FDA for advanced HCC (32,33). However, its anticancer efficacy is poor (34). Ubiquitin proteasome system (UPS) participates in a wide variety of biological processes which include cell cycle, cell proliferation, signal transduction, DNA repair and apoptosis (35).…”
Section: Discussionmentioning
confidence: 99%